Kepemimpinan Para Rasul Teladan Bagi Kepemimpinan Kristen Masa Kini Berdasarkan Kisah Para Rasul 1-6 - Ferri Melki Pandeirot; Tjutjun Setiawan; Rinawati (Sekolah Tinggi Teologi Sola Gratia Indonesia, 2023)
Leadership is an ever-present topic that can be found in almost any knowledge discipline. Good or bad fate of society or mankind is determined by its leaders. This research examines how the spiritual condition of the Apostles after Jesus was ascended to heaven. After Jesus was ascended to heaven, the apostles and followers of Jesus lost a figure, a leader, an example giver who guided their lives. This situation could have affected the spiritual condition and firmness in holding all the teachings and commands of Jesus; how their leadership was when facing Jewish leaders, priests, chief guards of the Temple, elders and scribes, the Religious Court and the Sadducees who generally hated them, as well as the attitude they showed to the public, especially the early church. This study uses a descriptive qualitative method with a literature study approach based on research on the Book of the Apostles 1-6. The purpose of this research is that today's ministers of God may learn how to behave correctly when they lose a role model and spiritual leader in their lives and how to continue Christian leadership through the example of the apostles and other disciples. Because actually the example of life is the main sermon for believers of all ages so that through the words and deeds of the Gospel of Jesus can be witnessed to the ends of the world, to be a blessing to many people. The author concludes that the example followed by the apostles from the Lord Jesus, the Great Teacher, can be shown through their leadership who relied on the Holy Spirit to the Jews and the early congregation who believed in the news of salvation. Even the leadership, attitude of life and example of the apostles became a culture in the early congregation so that it became a magnet and extraordinary movement for the development of Christians in the early years of the Christian era. The leadership of the apostles has also animates and changes the lives of many people and raises many leaders who love Christ. ABSTRAK BAHASA INDONESIA Kepemimpinan adalah topik yang selalu ada dan dapat dijumpai di hampir semua disiplin ilmu. Baik buruknya nasib masyarakat ataupun umat manusia ditentukan oleh pemimpinnya. Penelitian ini mengkaji bagaimana kondisi kerohanian Para Rasul setelah Yesus terangkat ke sorga, Sejak Yesus terangkat ke sorga, para rasul dan murid-murid Yesus yang lain kehilangan figur, sosok pemimpin, pemberi teladan yang menuntun kehidupan mereka. Situasi ini bisa saja mempengaruhi kondisi kerohanian serta keteguhan dalam memegang semua ajaran dan perintah Yesus; bagaimana kepemimpinan mereka ketika menghadapi pemimpin Yahudi, imam-iman, kepala pengawal Bait Allah, tua-tua dan ahli Taurat, Mahkamah Agama serta orang-orang Saduki yang secara umum membenci mereka, juga sikap yang mereka tunjukkan pada orang banyak terutama jemaat mula-mula. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan studi kepustakaan berdasarkan penelitian pada Kitab Para Rasul 1-2. Tujuan dari penelitian ini agar para pelayan Tuhan masa kini boleh belajar bagaimana bersikap yang benar ketika kehilangan sosok teladan dan pemimpin rohani dalam kehidupan mereka dan bagaimana melanjutkan kepemimpinan Kristen lewat teladan para rasul dan murid-murid lainnya. Sebab sesungguhnya teladan hidup adalah khotbah yang utama bagi orang percaya segala zaman sehingga lewat perkataan dan perbuatan Injil Yesus boleh disaksikan sampai ke ujung dunia, menjadi berkat bagi banyak orang. Penulis mengambil kesimpulan bahwa teladan yang diikuti oleh para rasul dari Tuhan Yesus sang Guru Agung, dapat ditunjukkan lewat kepemimpinan mereka yang mengandalkan Roh Kudus pada orang-orang Yahudi serta jemaat mula-mula yang percaya akan berita keselamatan. Bahkan kepemimpinan, sikap hidup dan teladan para rasul menjadi suatu budaya pada jemaat mula-mula sehingga menjadi magnet dan kegerakkan yang luar biasa bagi perkembangan umat Kristen pada awal tahun Masehi. Kepemimpinan para rasul juga telah menjiwai dan mengubah hidup banyak orang serta memunculkan banyak pemimpin yang mengasihi Kristus.